Large‐Area Fabrication of Highly Tunable Hybrid Plasmonic–Photonic Structures Based on Colloidal Lithography and a Photoreconfigurable Polymer. Issue 19 (20th June 2019) - Wang, Shiqiang; Dong, Hao; Sun, Fuwei; Zhang, Wanlin; Liang, Yun; Tian, Li; Wang, Peng; Yin, Xianpeng; Li, Guangtao
Abstract: In this work, based on colloidal lithography, a strategy is developed to produce a new type of hybrid plasmonic–photonic system comprising a periodic array of nanoholes in a photoreconfigurable polymer layer deposited on a gold surface. By controlling the experimental conditions, the geometric parameters of the nanoholes can be easily adjusted; hence, the optical properties of the systems are widely tunable. Importantly, the shape and topology of the round nanohole arrays can be easily reconfigured with proper photoirradiation, providing a means to modulate the optical properties and produce new functionalities, as exemplified by the formation of arrays with anisotropic or gradient structural features. Moreover, rubbing dielectric spheres into the formed nanoholes can further tune the topological structures of the dielectric components in the hybrid system, leading to a dramatic modification of the spatial energy distributions and inducing the formation of uniform electromagnetic fields confined near the embedded sphere surfaces, which are more beneficial for practical applications. All the results indicate that the combined use of the unique properties of both a photoreconfigurable polymer and colloidal lithography opens a new avenue with great potential for efficient and large‐area fabrication of hybrid plasmonic–photonic systems with a high degree of optical tunability. Abstract : A new type of highly tunable hybrid plasmonic–photonic system comprising a periodic array of nanoholes in a photoreconfigurable polymer layer deposited on a gold surface is developed. Besides the geometry, the shape and surface topology of the round nanohole arrays can be easily reconfigured under light irradiation, providing a high freedom for tuning the optical properties and generating new functionalities.